Dynamic Mechanical Thermal Analysis of Wood Polymer Composite Endurance to Prolonged Ultra Violet Irradiation Exposure - Shahrizan M.Z., A.; Zafiah M. Rus, Anika; Munirah A., Nur; Zulkhairi J., M.; Afiqah Sufian, N.; Saddam Kamarudin, N.; Marsi, N.; Aida Ibrahim, Siti; Hazwanee M.J., Farhana; F.L. Abdullah, M. (International Journal of Engineering and Technology, 2018)
This study was constructed to examine the viscoelastic properties and the microstructure of wood-plastic composites (WPCs) before and after being subjected to UV irradiation. The pellet of the wood polymer composites consists of polypropylene as the matrix and rice-husk flour as the reinforcing filler. The samples were UV irradiated from 5000 hours to 20,000 hours with the increment of 5000 hours to study the effect of weathering on the viscoelastic properties of the WPCs. The microstructures of the surface of the samples were examined using Optical Microscopy (OM). The mechanical properties of WPCs through dynamic mechanical analysis test were assessed for both polyvinyl chloride (PVC) and polypropylene (PP) samples. The value of storage modulus (Eâ€™) decreases when been exposed in the ultra violet irradiation, in both glassy and rubbery states. Moreover, the density of the WPC samples is closed to light weight and result is comparable. As for morphological properties test, the surface of cracked, voids appeared at the surface of the WPC samples of both PVC and PP interface and the density of composite decreased.Â Â